Summary of grazing research on Kansas CRP land - Michael R. Langemeier; P.D. Ohlenbusch; R.D. Jones (Kansas Agricultural Experiment Station Research Reports, 1997)
Animal performance and n et return per acre were examined for four CRP research sites in Kansas in 1 994, 1995, and 1996. Both mowing and prescribed burning increased animal performance in 1994. Mowing was economically feasible on one of the four sites. Prescribed burning was economically feasible on three of four sites. Mowing and burning treatments were not repeated i n 1995 or 1996. Net returns per acre for the site that was grazed with cowcalf pairs ranged from -$8.55 to -$25.54. For the sites grazed with stockers, net returns per acre varied from -$18.67 to $31 .39. Net returns per acre for stockers averaged $14.2 2 in western Kansas and $16.93 in central Kansas. Based on this research, grazing stockers on post-CRP land appears to have more potential than grazing cow-calf pairs.
Keywords: Cattlemen' s Day; 1997; Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 783; Beef; Conservation Reserve Program; Cow/Calf grazing; Stocker grazing